Comprehensive analysis of partial confounding clinical symptoms and treatment options of botulism: a case series - Huang, Xuanyu; Hu, Zhiping; Xiao, Han; Huang, Yan (Frontiers in Neurology, 2025)
ObjectiveTo examine the clinical presentations, and therapeutic principles of botulism, with the goal of improving physicians’ understanding of the condition and refining treatment strategies.MethodA retrospective analysis was carried out on the clinical data of 8 patients with botulism, encompassing age, gender, etiology, delay diagnosis time, course of disease, clinical manifestations, auxiliary examinations, and treatment.ResultsAmong the 8 cases, 5 were female and 3 male, with the age ranging from 14 to 60 years. 5 cases were of iatrogenic poisoning, and 3 were of foodborne poisoning. Besides the classical clinical manifestations, some patients had atypical symptoms like intestinal obstruction, unilateral involvement, and consciousness disorder. Among the 8 cases, 6 had abnormal electrophysiological examination results. 6 patients had a delayed diagnosis of over 7 days, with disease course from 7 to 115 days, and 7 received treatment. All patients received symptomatic and supportive treatment. Moreover, 4 received invasive respiratory support, 3 received intravenous immunoglobulin injection, 1 received plasma exchange therapy, and 1 received antitoxin therapy. All patients were discharged with normal cranial nerve function, gastrointestinal function, muscle strength, and tone.ConclusionPatients with botulism may exhibit atypical clinical symptoms, necessitating heightened vigilance from physicians. Neurophysiological studies are integral to the diagnostic process. Furthermore, symptomatic supportive treatment is essential for patients whose diagnosis has been delayed beyond 7 days. In conclusion, a comprehensive understanding of the clinical features, differential diagnostic criteria, and therapeutic options for botulism is essential for reducing disease duration, optimizing patient outcomes, and enhancing treatment efficacy.